30th Anniversary of the 1988 Judicial Crisis: Lessons about the Importance of Judicial Independence and Impartiality - Saleem Faruqi, Shad (Journal of Malaysian and Comparative Law, 2018)
Emeritus Professor Datuk Dr. Shad Saleem Faruqi is the Holder of the Tunku Abdul Rahman Chair, at the Faculty of Law, University of Malaya, and a Member of the Judicial Appointments Commission. This is an edited text of the Lecture presented at the Fifth Raja Aziz Addruse Memorial Lecture at the International Malaysian Law Conference 2018, 15 August 2018 at The Royale Chulan, Kuala Lumpur, Malaysia.